PENSADORES DA ALIMENTAÇÃO: TRABALHADORES DEBATEM SUAS DIFICULDADES PARA INCORPORAR PRÁTICAS ALIMENTARES SAUDÁVEIS - Mariana Maia Melo; Michelle Cristine Medeiros da Silva; Karine Cavalcanti Mauricio de Sena Evangelista; Fernanda Rafaella de Melo Silva (Universidade do Estado do Rio de Janeiro, 2016)
Chronic non-communicable diseases have been the cause of more than half of deaths in the world, and, among many other diseases, obesity. One of the factors for the increase in obesity is unhealthy eating habits, and this study has aimed to present an educational diagnosis of the difficulties found by workers at a Pediatric Hospital at Brazilian Federal University of Rio Grande do Norte to incorporate healthy eating habits in their daily lives. Eating involves cultural, social, emotional and sensory aspects, making people eat seeking not only nutrients but also the significance of the chosen food. Thus, a food and nutrition education intervention should include these aspects and be preceded by an educational diagnosis, to address the question of intrinsic human subjectivity to eating. To trace this educational diagnosis, focus group sessions were addressed with 14 research subjects to obtain data on the basis of discussion focused on a specific theme. As a result, it is possible to list five categories of problems: "no time," "entrenched eating habits," "lack of access to healthy lifestyles," "tasty is unhealthy," and "dieting is a sacrifice." Therefore, nutritional food education strategies must take place focused on self-care and adequate food as an expression of citizenship. Furthermore, it is suggested that healthy eating practices be encouraged and promoted in the workplace.       DOI: 10.12957/demetra.2016.16789